A.A. Vlasov and collisionless Landau damping - Rukhadze, A.A. (Вопросы атомной науки и техники, 2015)
The main results obtained by A.A. Vlasov in 1944 and published in 1945 are presented. The solution of the initial problem for small perturbations of the longitudinal field in collisionless plasma is givn. For the example of the model function of electron velocity distribution is shown that small perturbations of the longitudinal electric field varies with the plasma frequency and decay with time due to their absorption by the plasma electrons. Thus, at least a year before the publication of the famous work L.D. Landau, by A.A. Vlasov was obtained the decrement for collisionless damping of plasma oscillations, known today as Landau damping.